Macroeconomic Analysis: Digitalization on the Labor Market in Islam (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This scientific paper aims to analyze Macroeconomics: The impact of digitalization of the labor market in Islam. The method used in this study is qualitative with in-depth literature analysis. The findings of this study provide an in-depth understanding by analyzing macroeconomics and government efforts to protect workers from the impact of digitalization are contained in the Employment Law Article 164 Paragraph (3). Islam in viewing digitalization today is accepting this development because it is considered a development of science and technology, as contained in Qs. Al-Anbiyat verse 80.